Isolation and Characterization of Clinical Triazole Resistance Aspergillus fumigatus in Iran - Faezezeh MOHAMMADI; Seyed Jamal HASHEMI; Seyed Mojtaba SEYEDMOUSAVI; Dorna AKBARZADE (Tehran University of Medical Sciences, 2018)
Background: Aspergillus fumigatus is a major cause of allergic syndromes, aspergilloma and life-threatening invasive infections in immunocompromised hosts. To date, a wide range of mutations in A. fumigatushave been described conferring azole-resistance, which commonly involves modifications in the cyp51A-gene (substitutions at codons G54, G138, P216, F219, M220, G448 and specifically codon L98 in combination with a 34-bp tandem repeat in the promoter region of the gene), the target for azole antifungals. We investigated the prevalence of azole-resistance in clinical A. fumigatus isolates obtained from patients in Iran during 2010 to 2014. Methods: Overall, 172clinical A. fumigatus isolates obtained from patients with underlying disease including transplantation, granulocytopenia, chronic liver disease, chronic obstructive pulmonary disease (COPD) and allergic bronchopulmonary aspergillosis (ABPA). Samples were collected between Jan 2009 and Nov 2014 from five provinces of Iran (Tehran, Shiraz, Isfahan, Khorasan razavi and East Azerbaijan). Antifungal susceptibility test was determined according to EUCAST reference method for itraconazole (ITC), voriconazole (VRC) and posaconazole (POS). All isolates were confirmed by amplification of the partial tubulin gene. Results: Of 172 A. fumigatus isolates tested, six isolates (3.5%) had high MIC values of ITC (>16 mg/L) and VRC (≥4 mg/L). All six isolates showed a multi-resistant phenotype with high MICs of ITC and VRC. Conclusion: We determined in-vitro susceptibility a profile of 172 clinically isolates of A. fumigatus against triazole in Iran. Azole-resistance is an emerging problem in A. fumigatus and international surveillance is warranted.